STUDENTS PERCEPTION OF ENGLISH CLUB IN ENHANCING COMMUNICATIVE SKILLS AT SMAN 1 MEMPAWAH HILIR IN THE ACADEMIC YEAR 2022/2023 - Bimantara, Yogi; Aunurrahman; Darajat, Ageung (Journal of English Language Teaching and Education (JELTE), 2024)
In the research titled "Students Perception Of English Club In Enhancing Communicative Skills At Sman 1 Mempawah Hilir In The Academic Year 2022/2023," the aim of this study is to determine the benefits of joining the English club and students' perceptions of the English club in improving their communication skills. In this research, the researcher employed two instruments to collect data: field notes and interviews. The study was conducted at SMAN 1 Mempawah Hilir and involved the extracurricular English club instructor, Yuli Nuranawati, S.Pd. The researcher collaborated with the extracurricular instructor in data collection, seeking assistance in observing English club students to avoid bias. Meanwhile, the interviews were conducted by the researcher. Six English club students were selected as interviewees. Based on the results of observations and interviews conducted by the researcher in collaboration with the extracurricular instructor, it was found that the English club had a positive impact on their communication skills. The researcher also discovered how the English club enhanced their communication abilities.